The Perception Of Clients In Rehabilitation Center On Inhalant Use - Amin Al Haadi Bin Shafie; Mohd Khairul Anuar Rahimi; Muhammad Harith Awaludin; Nurul Ashikin Ahmat Miskam; Farhana Sabri; Noorazimah Kamaruddin; Mizan Adiliah Ahmad Ibrahim; Hishamuddin Abdul Wahab; Mohd Radhi Ibrahim (Human Resource Management Academic Research Society, 2024)
Indexed by ERA